Design: logo : an exploration of marvelous marks, insightful essays and revealing reviews - Howalt, Paul; Glitschka, Von (Design portfolios (Rockport Publishers), 2014)
"It's inevitable. At some point in your career as a designer, you're bound to work on a logo. Design: Logo, the exciting new book in our Design: series, is an inspirational resource created for everyone who works or wants to work on logo design. Design: Logo showcases over 300 eye-catching logo designs chosen by two leading identity designers. In addition to being an inspirational guide, this book also includes helpful information such as "Close Ups," in which the authors dissect 20 projects and point out the details that make each so successful, and five insightful essays by prominent logo designers. This must-have resource puts inspiration right in your hands, allowing you to peruse your ideas and see what other designers are doing in the field. With over 300 exemplary logo designs, you'll be primed and ready to create outstanding designs of your own."--